Optimisation Models and Algorithms for Real-life Transportation Routing and Scheduling Problems - Chen, Binhui (2018)
This thesis investigates the transportation routing and scheduling problems derived from the container transportation in Ningbo Port, which is the second largest port in China. In the container transportation problem, a fleet of trucks are scheduled to accommodate a sequence of container transshipment requests among multiple container terminals. This problem closely relates to the classic vehicle routing problem with time windows (VRPTW) in which the customers are routed to be serviced with minimal cost, satisfying capacity and time constraints. Facing the fast growing throughput in the port, an efficient automatic routing and scheduling system is urgently needed. In the Ningbo Port problem, there are mainly two types of transshipment requests (long-distance and short-distance) need to be scheduled to optimise fleet usage, while the transportation cost for the two types of tasks are different. As a result, to promote the vehicle utility and reduce operational cost at the same time, not only producing solutions of high quality are pursued in this research but also advanced problem modelling methods.